Improving Students Mathematical Critical Thinking Ability With Learning Modules Using Brain-Based Learning Models - Nisa Ulkhairat Asfar; Dony Permana; Ahmad Fauzan; Yarman Yarman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The quality of mathematics learning is influenced by good teaching material and can facilitate students to be active in knowledge and improve mathematical critical thinking skills. Mathematical critical thinking skills focus on activities in analyzing a more specific idea. Developing a learning module using a brain-based learning model is necessary to improve mathematical critical thinking skills. This study aims to determine the characteristics of the learning module using a brain-based learning model that is valid, practical, and effective. This type of research is development research using the Plomp model, which consists of three stages, namely the preliminary, development, and assessment stages. The module is made using a Brain-based learning model for class X Junior High School (SMA). The instruments used are validation sheets, observation sheets, questionnaires, interviews, and tests. The results showed that the learning module using the brain-based learning model for class X SMA was valid, practical, and effective. The validity of the module reaches 78.6. In contrast, the practicality of the module is 91.67%. In terms of effectiveness, it can be seen from students' average mathematical critical thinking ability test results, namely from 52.2 to 88.1